Air quality management - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 1997)
The management of air quality is currently at the forefront of international debate. With authors drawn from international experts in their respective fields, Air Quality Management provides comprehensive coverage of the air quality management issue. There are chapters on improving air quality in the UK, the construction of emissions inventories and the design and operation of air monitoring networks. Validation of air pollution models, requiring source receptor modelling, is described, as is the use of geochemical or biological tolerances known as critical loads to determine the maximum allowable inputs of pollutants to the terrestrial environment. The first European Auto-Oil Study, which was sponsored by the European Commission in order to identify the most cost-effective means of meeting air quality targets, is included as a case study. There is also reference to the successes and problems of air pollution control in California, the US state which has pioneered the promotion of vigorous air pollution control measures. Air Quality Management provides a vital source of material for all those involved in the field, whether as a student, industrialist, consultant, or government agency with responsibility in this area.
Keywords: Air quality management.; elektronické knihy; electronic books